Immunohistochemical subtypes predict survival in metastatic breast cancer receiving high-dose chemotherapy with autologous haematopoietic stem cell transplantation. (April 2016) - Boudin, Laurys; Chabannon, Christian; Sfumato, Patrick; Sabatier, Renaud; Bertucci, François; Tarpin, Carole; Provansal, Magali; Houvenaegel, Gilles; Lambaudie, Eric; Tallet, Agnes; Resbeut, Michel; Charafe-Jauffret, Emmanuelle; et al.
Abstract: Introduction: The objective of this study was to evaluate the outcome of patients affected with different subtypes of metastatic breast cancer (MBC) following treatment with high-dose chemotherapy (HDC) and autologous haematopoietic progenitor cell transplantation (AHSCT). Methods: All consecutive female patients treated for MBC with HDC and AHSCT at the Institut Paoli-Calmettes between 2003 and 2012 were included. Patient, tumour and treatment characteristics were collected. Patients were categorised in three subtypes based on hormonal receptor (HR) and human epidermal growth factor receptor 2 (HER2) status of the primary tumour: luminal (L), (HR+/HER2–), HER2 (HER2+, any HR), and triple negative (TN) (HER2– and HR–). The main objective was the analysis of overall survival (OS) according to the immunohistochemical (IHC) subtypes. Results: A total of 235 patients were included, median age was 46 (range 21–62). Median follow up was 53.28 months (95% confidence interval [CI] 45.12–57.6). The TN subtype appeared to have the worst prognosis with a median OS of 19.68 months (95% CI 11.76–44.4) compared to 44.64 months (95% CI 40.32–67.56) for the luminal subtype and a median OS not reached for the HER2 subtype (p < 0.01). In the multivariate analysis, the TN subtype retained an independent poor prognosis value compared to the luminal subtype, with a hazard ratio of 2.03 (95% CI 1.26–3.29, p = 0.037). Conclusion: HDC-AHSCT does not change the prognostic value of IHC subtypes in MBC patients. OS favourably compares with data available in the literature on similar groups of patients. These findings provide additional information and options for patients with MBC and who could potentially benefit of HDC-AHSCT. Highlights: We examine the outcome of a modern population of metastatic breast cancer (MBC) receiving high-dose chemotherapy and autologous haematopoietic progenitor cell transplantation (HDC-AHSCT). Median progression-free survival and overall survival compare favourably with results for conventional therapy. HDC-AHSCT does not change the prognostic impact of the different breast cancer subtypes. HDC-AHSCT does not impact on management after relapse of MBC.